THE ANALYSIS FACTORS OF CAPITAL ADEQUACY ON INDONESIA “BUKU-4” BANK CATEGORY - Hardiyanti, Siti Epa (LLDIKTI Wilayah 1 Sumatera Utara, 2024)
In this paper, the researcher contribute to extending the prior literature on the bank BUKU Category by investigating the influence of capital adequacy ratio factors. On the previous studies, the factors of banking capital adequacy ratio can be influenced by several factors such as Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), and Size. In previous research stated that NPL and LDR as partially had a negative effect on the Capital Adequacy Ratio, ROA and Size had a positive effect on the Capital Adequacy Ratio level. In this study, the researchers used seven sample of commercial banks included in the Bank BUKU-4 Category as commercial banks with huge capital category in the 2018-2022 period. As Random Effect Model (REM) chosen to be the estimation model. Our findings provide empirical support on the findings researh of Azizah and Taswan's research, that simultaneously the NPL, LDR, ROA and SIZE have an influence on the capital adequacy ratio level of Commercial Banks which are included in the BUKU-4 bank category. However, partially, the influence of the independent variables on the dependent variable is differences. NPL has an influence on CAR, LDR has a negative influence on CAR, ROA has a positive influence on CAR, and Size has a negative influence on CAR. The implication of this research is that when commercial banks included on the BUKU-4 Bank category, the commercial banks that included on BUKU-4 Bank category are banks that are considered stable with a capital capacity of more than 70 trillion rupiah so that the NPL, LDR and Size levels have no larger effect. Because the huge of commercial banks which is included are whose financial levels are stable so that not has a big impact on the level of capital adequacy in BUKU-4 category commercial banks, the level of profit obtained by these banks. However, it does not rule out the possibility that apart from the variables that have been studied, there are other variables that can have a big influence on the level of capital adequacy other than those mentioned by the researchers in this study